Roles of Circular RNAs in Neurologic Disease - Shao, Yiye; Chen, Yinghui (Frontiers in Molecular Neuroscience, 2016)
Circular RNAs (circRNAs) are a novel type of endogenous noncoding RNA receiving increasing attention. They have been shown to act as a natural microRNA sponges that repress the activity of corresponding miRNAs by binding with them, thus regulating target genes. Numerous studies have shown that miRNAs are involved in the pathogenesis of neurological disease. Therefore, circRNAs may act as important regulatory factors in the occurrence and development processes of neurological disease.